Medical Treatment for Severe Ulcerative Colitis - Iizuka, M.; Igarashi, K.; Chiba, M.; Kodama, K.; Tsurui, N.; Horie, Y.; Masamune, O. (Nippon Daicho Komonbyo Gakkai Zasshi, 1989)
The results of medical treatment of 9 patients with severe ulcerative colitis are reported ; 5 patients obtained remission with medical therapy, while 4 needed surgical intervention. One patient died after a second operation. Two of the 5 patients who obtained remission with medical treatment did not respond to the initial dose of prednisolone (30 mg/day), but did respond to increased dosages (49-60 mg/day). Another patient obtained remission with prednisolone given intravenously (60 mg) and intraarterially (40 mg). Indications for surgical treatment in the other 4 cases were as follows ; 1) two patients did not respond to medical treatment, 2) a third patient had chronic persistent colitis and underwent surgery without active medical treatment, and 3) the fourth patient had associated cecal perforation. The present regimen used for treatment of severe ulcerative colitis in our department is as follows ; prednisolone 60 mg or more (i. v. or p. o.) followed by prednisolone 40 mg (i. a.). If colitis does not subside as a result of these treatments, then surgical intervention is carried out without delay.